Review of TORRANO, J. (2022) Eurípides. Teatro Completo II: Os Heraclidas, Hipólito, Andrômaca, Hécuba. São Paulo, Editora 34 - Rocha Rachid, Rodolfo José (Revista Archai, 2024)
Review of TORRANO, J. (2022) Eurípides. Teatro Completo II: Os Heraclidas, Hipólito, Andrômaca, Hécuba. São Paulo, Editora 34.